Machine learning models combining computed tomography semantic features and selected clinical variables for accurate prediction of the pathological grade of bladder cancer - Deng, Zhikang; Dong, Wentao; Xiong, Situ; Jin, Di; Zhou, Hongzhang; Zhang, Ling; Xie, LiHan; Deng, Yaohong; Xu, Rong; Fan, Bing (Frontiers in Oncology, 2023)
The purpose of this research was to develop a nomogram that combines several radiomic features to predict the pathological grade of bladder cancer (BCa) using non-enhanced computed tomography (NE-CT) scanning images before surgery.